Are couple communication and marital satisfaction associated with parental self-efficacy? : focusing on Korean mothers of 2 to 5 year old children? - Kim, Sanghoon (2018)
Mothers’ parental self-efficacy (PSE) tends to be associated with children’s behavioral and psychological development and may predict academic achievement. The purpose of the present study is to seek whether the quality of mothers’ communicative ability and couple relationship may be linked to their parental self-efficacy. This study aims to examine the relationships among Korean mothers’ cou-ple communication ability (CCA), marital satisfaction (MS) and parental self-efficacy (PSE). The current study also investigated whether CCA and MS predict PSE among Korean mothers. In addition, the study further explored the possible association between interaction time between partners in a couple setting and mothers’ CCA, MS and PSE. The participants of this study were 111 mothers from Seoul, South Korea, with children aged 2 to 5-year-old. The mothers answered the self-evaluation questionnaires with respect to CCA, MS and PSE as well as weekly interaction hours with their husbands. Results of this study demonstrated that mothers’ CCA, MS and PSE were significantly related. Second, the mothers’ CCA and MS can predict their PSE with CCA having a higher contribution on PSE than MS. Third, the mothers those who spend more than 1 hour for interacting with their husbands tend to have higher CCA and MS, but not PSE, than those who spend less than 1 hour. The results of the study indicating an important role of CCA to PSE can be utilized for parental education programs.